Deciding to Disclose a Mental Health Condition in Male Dominated Workplaces; A Focus-Group Study - Stratton, Elizabeth; Einboden, Rochelle; Ryan, Rose; Choi, Isabella; Harvey, Samuel B.; Glozier, Nicholas (Frontiers in Psychiatry, 2018)
Objectives Deciding to disclose a mental illness in the workplace requires thoughtful informed decision making. Decision aids are increasingly used to help people make complex decisions, but need to incorporate relevant factors for the context. This study aimed to identify factors and processes that influence decision making about such disclosure to inform the development a disclosure decision aid tool for employees in male dominated industries. Methods We invited 15 partner organisations in male dominated industries to facilitate the recruitment of employees who either had disclosed a mental health condition in their workplace; or occupied a position to whom employees disclosed to focus groups addressing the aims. Results The majority of the organsiations had explicit policies that employees must disclose and so were unable to be seen countenancing non-discloure as an option. Two focus groups were conducted (n=13) with mainly male (62%), full-time employed (85%) employees, and both disclosed (46%) and authority (54%). Six themes, all barriers, were identified as influencing decision making processes: knowledge about symptoms, and self-discrimination (internal), stigma and discrimination by others, limited managerial support, dissatisfaction with services, and/or a risk of job or financial loss (external). Conclusion Decisions to disclose mental health conditions, even by those who had done so, appear driven entirely by consideration of negative aspects. This suggests that anti-discrimination policy, legislation, awareness campaigns, and manager training have yet to change negative perceptions, and that any decision aid tool needs to incorporate counterfactual positive aspects that appear not to be an important consideration in such male dominated workplaces. There is a disconnect between organisational policies favouring disclosure and employees favouring non-disclosure that has caused tension within the organisational culture. Decsion aid tools may assist employees with an active disclosure without waiting for an event to occur, giving the control of the decision back to the employee.